Social functioning in major depressive disorder. (October 2016) - Kupferberg, Aleksandra; Bicks, Lucy; Hasler, Gregor
Abstract: Depression is associated with social risk factors, social impairments and poor social functioning. This paper gives an overview of these social aspects using the NIMH Research and Domain Criteria 'Systems for Social Processes' as a framework. In particular, it describes the bio-psycho-social interplay regarding impaired affiliation and attachment (social anhedonia, hyper-sensitivity to social rejection, competition avoidance, increased altruistic punishment), impaired social communication (impaired emotion recognition, diminished cooperativeness), impaired social perception (reduced empathy, theory-of-mind deficits) and their impact on social networks and the use of social media. It describes these dysfunctional social processes at the behavioural, neuroanatomical, neurochemical and genetic levels, and with respect to animal models of social stress. We discuss the diagnostic specificity of these social deficit constructs for depression and in relation to depression severity. Since social factors are importantly involved in the pathogenesis and the consequences of depression, such research will likely contribute to better diagnostic assessments and concepts, treatments and preventative strategies both at the diagnostic and transdiagnostic level.